Evolution of Left Atrial Thrombus with Anticoagulant Therapy -Follow-up by Transesophageal Echocardiography - Kim, Cheol-Ho (Korean J Intern Med, 1995)
OBJECTIVES: Atrial fibrillation is an important risk factor for systemic embolism. A number of clinical studies demonstrated the beneficial effect of anticoagulant therapy for the prevention of embolism. But there has been no study on the fate of left atrial thrombus demonstrated by transesophageal echocardiography in the course of anticoagulation therapy. METHODS: Thirteen patients, demonstrated to have left atrial thrombus by transesophageal echocardiography were followed with anticoagulation therapy. Repeated transesophageal echocardiography was done 15 months after 1st study. RESULTS: Among 9 patients with adequate anticoagulation effect (INR>2.0), left atrial thrombus disappeared in 3 patients. The size of thrombus decreased from 2.2±0.8cm to 0.9±1.0cm (p<0.05 by paired Student’s t-test). CONCLUSIONS: Left atrial thrombus could dissolve or decrease in size with adequate anticoagulation.